Restorative Justice For Perpetrators Of Crimes (Jarīmah) In The Perspective Of Islamic Law - Fahmi, Mutiara (Universitas Islam Negeri Ar-Raniry, 2025)
Restorative justice is an alternative resolution of criminal cases which aims to create an agreement on the resolution of criminal cases that is fair and balanced for all parties, both victims and perpetrators. This process also focuses on restoring the original situation and restoring patterns of peaceful relations in society through dialogue and mediation. This paper aims to examine whether the process of resolving criminal cases in Islam can implement restorative justice mechanisms? If so, what are the requirements? The answers to these two questions are very important to study considering that the implementation of criminal law in Aceh adheres to the Islamic criminal law system (Qanun Jināyāt) which in practice also intersects with the national legal system. This qualitative research is a normative legal study whose presentation uses a descriptive analysis method. Primary data were collected through a literature review from various sources of classical Islamic law references (fiqh mazhab) and laws and regulations (positive law). Research results show that The restorative justice for the perpetrators of jarīmah in Aceh in the view of Islamic law can be done as long as it has not been included in the formal examination of the case by the Judge. Besides that, The Restorative justice can be applied to jarīmah ta'zīr and hudūd which are related to the rights of the servant, and not the rights of Allah. The researcher suggests peaceful efforts through Restorative Justice are strongly recommended by Islamic legal system to avoid the emergence of a sense of resentment and injustice as a result of the judge's decision that could arise from the victim or perpetrator. Diversion efforts with a Restorative Justice approach in cases of children in conflict with the law are in line with the spirit of Islamic law which prioritizes the principles of justice for all parties and maintains peace, especially when criminal penalties cannot be imposed due to insufficient age requirements for children in conflict with the law. Keywords: Restorative Justice – Jarīmah – Islamic Law